Liquid profiling of circulating tumor DNA in colorectal cancer: steps needed to achieve its full clinical value as standard care - Hedtke, Maren; Pessoa Rejas, Rodrigo; Froelich, Matthias F.; Ast, Volker; Duda, Angelika; Mirbach, Laura; Costina, Victor; Martens, Uwe Marc; Hofheinz, Ralf-Dieter; Neumaier, Michael; Haselmann, Verena (Molecular oncology, 2022)
The analysis of circulating tumor DNA (ctDNA) is at the threshold of implementation into standard care for colorectal cancer (CRC) patients. However, data about the clinical utility of liquid profiling (LP), its acceptance by clinicians, and its integration into clinical workflows in real-world settings remain limited. Here, LP tests requested as part of routine care since 2016 were retrospectively evaluated. Results show restrained request behavior that improved moderately over time, as well as reliable diagnostic performance comparable to translational studies, with an overall agreement of 91.7%. Extremely low ctDNA levels at < 0.1% in over 20% of cases, a high frequency of concomitant driver mutations (in up to 14% of cases), and ctDNA levels reflecting the clinical course of disease were revealed. However, certain limitations hampering successful translation of ctDNA into clinical practice were uncovered, including the lack of clinically relevant ctDNA thresholds, appropriate time points of LP requests, and integrative evaluation of ctDNA, imaging, and clinical findings. In conclusion, these results highlight the potential clinical value of LP for CRC patient management and demonstrate issues that need to be addressed for successful long-term implementation in clinical workflows.